2013
DOI: 10.1021/ma301526a
|View full text |Cite
|
Sign up to set email alerts
|

Role of Interfacial Structure of Water in Polymer Surface Wetting

Abstract: We present a theoretical approach to investigate the structures and contact angles of water in contact with different polymer surfaces. In the theoretical approach, the three-dimensional reference interaction site model integral equation and the three-dimensional density functional method are combined through the bridge function. First, the threedimensional distribution functions of water over the crystalline polyethylene surface and the amorphous polyethylene, polypropylene and polystyrene surfaces are calcul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 49 publications
0
10
0
1
Order By: Relevance
“…The water molecules related to those functions exist in the vicinity of the polymers and, compared to bulk water, have different properties, which have been studied by various techniques such as differential scanning calorimetry (DSC), 1 , 2 neutron reflectometry, 3 5 atomic force microscopy, 6 and contact angle measurements. 7 , 8 Vibrational spectroscopy has been used to analyze the structural and dynamical properties of aqueous solutions. 9 14 The state of water in various polymers has often been studied by analyzing the OH stretching bands obtained from IR spectroscopy, 15 19 with the expectation that abundant information with regard to the nature of hydrogen bonding is contained in the band shapes.…”
Section: Introductionmentioning
confidence: 99%
“…The water molecules related to those functions exist in the vicinity of the polymers and, compared to bulk water, have different properties, which have been studied by various techniques such as differential scanning calorimetry (DSC), 1 , 2 neutron reflectometry, 3 5 atomic force microscopy, 6 and contact angle measurements. 7 , 8 Vibrational spectroscopy has been used to analyze the structural and dynamical properties of aqueous solutions. 9 14 The state of water in various polymers has often been studied by analyzing the OH stretching bands obtained from IR spectroscopy, 15 19 with the expectation that abundant information with regard to the nature of hydrogen bonding is contained in the band shapes.…”
Section: Introductionmentioning
confidence: 99%
“…The results are shown in Figure 3. According to our previous investigations, 34,35 high-density peaks correspond to low local free energy. In the case of a strong solvophobic state, it is shown that the nucleated droplets on the smooth (Figure 3a) and microrough (Figure 3b) surfaces display similar morphology outside the liquid−solid interface.…”
Section: Resultsmentioning
confidence: 58%
“…35 Two typical successes of the RISM for quantitative calculation are the hydration free energy 36,37 and surface wetting. 38 In this work, we try to propose a new theoretical procedure to analyze the thermodynamics of ice crystallization by combining the merits of the RISM and the classical DFT. During the theoretical calculations, the crystal−liquid phase equilibria need to be predicted in advance.…”
Section: ■ Introductionmentioning
confidence: 99%